Physical demand of seven closed agility drills. Issue 4 (1st October 2016) - Atkinson, Mark; Rosalie, Simon; Netto, Kevin
Abstract: The present study aimed to quantify the demand of seven generic, closed agility drills. Twenty males with experience in invasion sports volunteered to participate in this study. They performed seven, closed agility drills over a standardised 30-m distance. Physical demand measures of peak velocity, total foot contacts, peak impacts, completion time, and maximum heart rate were obtained via the use of wearable sensor technologies. A subjective rating of perceived exertion (RPE) was also obtained. All measures, with the exception of maximum heart rates and RPE were able to delineate drills in terms of physical and physiological demand. The findings of this study exemplify the differences in demand of agility-type movements. Drill demand was dictated by the type of agility movement initiated with the increase in repetitiveness of a given movement type also contributing to increased demand. Findings from this study suggest agility drills can be manipulated to vary physical and physiological demand. This allows for the optimal application of training principles such as overload, progression, and periodisation.